2010
DOI: 10.1002/hed.21576
|View full text |Cite
|
Sign up to set email alerts
|

BMI1'S maintenance of the proliferative capacity of laryngeal cancer stem cells

Abstract: BMI1 was required to maintain the proliferative capacity of laryngeal CSCs, which may be a molecular target to cure patients with laryngeal SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
4
35
1
Order By: Relevance
“…36 Prior studies showed that CD44 and CD133 had been used to isolate CSCs from multiple tumor types. 21,[37][38][39] However, in the present study, both of the cell lines presented as CD44 high , and showed only 0.53% of the SCC9-S cells expressed CD133, in contrast to 0.06% of the SCC9-N cells. With these findings in mind, a 'stemness' marker that works well in one cancer may not apply to other types of cancers.…”
Section: Discussioncontrasting
confidence: 44%
“…36 Prior studies showed that CD44 and CD133 had been used to isolate CSCs from multiple tumor types. 21,[37][38][39] However, in the present study, both of the cell lines presented as CD44 high , and showed only 0.53% of the SCC9-S cells expressed CD133, in contrast to 0.06% of the SCC9-N cells. With these findings in mind, a 'stemness' marker that works well in one cancer may not apply to other types of cancers.…”
Section: Discussioncontrasting
confidence: 44%
“…Its knockdown resulted in inhibition of in vitro proliferative, clonogenic, invasive capacity, and in vivo tumorigenic potential of CD133+ cells through up-regulation of p16(INK4A) and p14(ARF) [57]. More importantly, BMI1 expression was demonstrated to be co-localized with CD133 in LCa specimens [52,58]. These findings suggested BMI1 as a molecular target to treat patients with LCa.…”
Section: Bmi1mentioning
confidence: 87%
“…As an initial study, Yu et al [55] demonstrated significant overexpression of oncogenic BMI1 protein,which involves in gene silencing, through chromatin modifications [55], in CD44+/CD133+ cells [34]. It was reported to be upregulated in laryngeal tumor tissue samples and CD133 positive Hep-2 cells, which provided maintenance of cell proliferation and prevented apoptosis [52,56]. Its knockdown resulted in inhibition of in vitro proliferative, clonogenic, invasive capacity, and in vivo tumorigenic potential of CD133+ cells through up-regulation of p16(INK4A) and p14(ARF) [57].…”
Section: Bmi1mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of CD133, have been associated with CD44+ expression in HNSCC and with Bmi1 induced proliferation in laryngeal carcinomas (Zhang et al, 2010;Chen et al, 2011;Sun et al, 2012). In fact, positive correlation of Oct-4, Nanog with an increased expression status of CD133 depicted a poorer prognosis for oral cancer patients (Chiou et al, 2008).…”
Section: Cd133mentioning
confidence: 98%